1975
DOI: 10.1017/s0025315400017227
|View full text |Cite
|
Sign up to set email alerts
|

Mucilage sheaths of spores of red algae

Abstract: Spores of fourteen species of red algae were examined in sea water/Indian ink suspensions and the volumes of the spores and their mucilage sheaths measured. The mucilage sheaths occupied 52-8-87-7% of the combined spore + mucilage volumes, depending on the species. Spores of different size of the same species had mucilage sheaths occupying similar proportions of the combined volumes, but spores of similar sizes from different species had mucilage volumes typical of all spores of the same species. Experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 9 publications
(19 reference statements)
5
16
0
Order By: Relevance
“…In many cases the release of the spores involves an active discharge mechanism, usually as a result of increased turgor pressure of the mucilage surrounding the spore within each sporangium (e.g. egg release in Tilopteris, Kuhlenkamp & Miiller, 1985; spore release in Laminariales, Toth, 1976b;Maier & Miiller, 1982; spore release in various red algae, Boney, 1975Boney, , 1981. In some algae, however, the reproductive spores are distributed whilst still attached to the parental plant body.…”
Section: Locating the Substratummentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases the release of the spores involves an active discharge mechanism, usually as a result of increased turgor pressure of the mucilage surrounding the spore within each sporangium (e.g. egg release in Tilopteris, Kuhlenkamp & Miiller, 1985; spore release in Laminariales, Toth, 1976b;Maier & Miiller, 1982; spore release in various red algae, Boney, 1975Boney, , 1981. In some algae, however, the reproductive spores are distributed whilst still attached to the parental plant body.…”
Section: Locating the Substratummentioning
confidence: 99%
“…Certainly it is a common and very tenacious component of red algal spores (Boney, 1975(Boney, , 1981Ngan & Price, 1979) and can be clearly seen under the light microscope using indian ink preparations. The trailing character of this mucilage during spore movement and its adhesive sticky nature enhances entrapment and provides an early attachment mechanism.…”
Section: Initial Attachmentmentioning
confidence: 99%
“…Little is known of the density of algal propagules and the measurements of Coon, Neushul & Charters (1972) and Okuda & Neushul (1981), are probably significant overestimates, for they made no allowance for the large mucilage envelopes that surround most red algal spores. These envelopes may constitute 80% of the spore's volume (Boney, 1975;Ngan & Price, 1979). It is unlikely that the mucilage usually slows the sinking rate of such spores, as is often claimed (e.g.…”
Section: Properties Of the Disseminulesmentioning
confidence: 88%
“…Santileces, 1990), since the increase in diameter is so great that sinking velocity will almost certainly be increased. Boney (1975), for example, observed that newly-released spores sank up to twice as fast as those held overnight during which time the diameter of the mucilage sheath had significantly diminished.…”
Section: Properties Of the Disseminulesmentioning
confidence: 99%
“…In many species of algae the mucilage disperses rapidly, but in others the spores, and sometimes the eggs or zygotes, possess a more or less persistant mucilage layer or sheath. Boney (1975) observed that the mucilage sheath could be voluminous and constitute up to 92% of the spore volume in some red algae, and he argued that the presence of Fl6s 7-12. Macroalgal propagule structure.…”
Section: Mucilagementioning
confidence: 99%